2013
DOI: 10.1002/rcs.1543
|View full text |Cite
|
Sign up to set email alerts
|

Robotic system with sweeping palpation and needle biopsy for prostate cancer diagnosis

Abstract: This system can be applied to detect hard materials such as tumor and malignant tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It had been reported that a robot could reliably detect the instant of needle puncture using coaxial force sensor without being affected by artifacts 21 . In reality, it is also easy to sense the tissue properties using free hand for skilled radiologists, such as the skin, the muscle, the ligament, etc 22 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that a robot could reliably detect the instant of needle puncture using coaxial force sensor without being affected by artifacts 21 . In reality, it is also easy to sense the tissue properties using free hand for skilled radiologists, such as the skin, the muscle, the ligament, etc 22 24 .…”
Section: Discussionmentioning
confidence: 99%
“…An aim of this work is to try to improve upon the sensitivity of trans‐rectal prostate biopsies which, due to the random nature of the biopsy protocol, can miss smaller cancers. Ahn et al took indentation testing results further and applied them to a robotic‐based prostate biopsy device which can obtain mechanical information about the target tissues, that can then be used to localize suspicious areas for biopsy. While some success in phantom models was achieved, tests on ex‐vivo prostates yielded poorer results, with sensitivity of the robotic‐indenter reaching only 42% and thus further work on this is required, in particular to account for the potential effect that the presence of rectal wall tissue and Denon Villiers fascial tissue may have on the probe.…”
Section: Methods Of Mechanical Characterizationmentioning
confidence: 99%
“…They, in particular, have shown that switching from point by point to sweeping can save examination time. Ahn et al [42,43] have developed a probe for prostate cancer diagnostics. This probe performs a rotational sweep and measures the force during the sweep.…”
Section: Plos Onementioning
confidence: 99%